A review on the Feasibility and Application of Geospatial Techniques in Geotechnical Engineering Field. (2022) - Khan, Farhan; Das, Bhumika; Ram Krishna Mishra, Sri; Awasthy, Mohan
Abstract: Geographic Information System (GIS) a new tool for digital data management, Graphical representation of areas with actual location, analysis, planning, designing of data and many more uses. To understand the application, significance, functions and scope of GIS a review has done, using reference of previous published research which will fill the gap between technology and techniques and gives a better idea about the different area and use of GIS in Geotechnical engineering. We have Search more than 100 research papers between 1980 and 2020 from different sources. The data relevant to the study was checked physically and rest discarded. From literatures different Data, methods, software's, limitation, and area of use is expected to determined. land use/landcover data, agricultural soil data, engineering soil data, environmental data, interpolation of data for missing data, ground water data and different types of data which have spatial value can be used to get different results. This review has explored scope of GIS in different field, their application and analysis methods. The systematic collection and identification of GIS Data can facilitate any project and save the time, cost, and effort and increase the accessibility to digital Maps, Bore log data, lithology etc. This study will definitely help the new researcher to proper understand the GIS and fill the research gap in areas where the GIS is used in lesser way or even not used in technical work.